2020
DOI: 10.1002/admi.201902168
|View full text |Cite
|
Sign up to set email alerts
|

Organic–Rare Earth Hybrid Anode with Superior Cyclability for Lithium Ion Battery

Abstract: new applications. Much effort is concentrated on design and synthesis of novel electrodes that possess high theoretical capacity, proper potential, and excellent structural stability during long-term cycling. [2] Considering the sustainable development, organic redox compounds with structural diversity should be ideal electrode materials. However, organic compounds frequently suffer from intractable technical challenges: [3] a) limited electroactive sites for Li-ions insertion/ desertion cause low specific ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Zhao et al [215] reported another molecular modification dwelling on substitution of oxygens in dicarboxylate scaffolds with sulfur atoms to form thiocarboxylate compounds as an alternative negative electrode materials for sodium batteries (Figure 7c). [215][216][217] The authors proposed three different chemistries: sodium dithioterephthalate (denoted as Na 2 -DTT), sodium tetrathioterephthalate (denoted as Na 2 -TTT), and sodium 4,4'-biphenyltetrathiodicarboxylate (denoted as Na 2 -BTTC). Contrary to conjugated dicarboxylates derivatives, which have a typical aspect of white powders (empirically attributed to poor electronic conductivity), the thiocarboxylate samples present darker coloring, an indication of intrinsic electrical conductivity.…”
Section: Other Molecular Modificationsmentioning
confidence: 99%
“…Zhao et al [215] reported another molecular modification dwelling on substitution of oxygens in dicarboxylate scaffolds with sulfur atoms to form thiocarboxylate compounds as an alternative negative electrode materials for sodium batteries (Figure 7c). [215][216][217] The authors proposed three different chemistries: sodium dithioterephthalate (denoted as Na 2 -DTT), sodium tetrathioterephthalate (denoted as Na 2 -TTT), and sodium 4,4'-biphenyltetrathiodicarboxylate (denoted as Na 2 -BTTC). Contrary to conjugated dicarboxylates derivatives, which have a typical aspect of white powders (empirically attributed to poor electronic conductivity), the thiocarboxylate samples present darker coloring, an indication of intrinsic electrical conductivity.…”
Section: Other Molecular Modificationsmentioning
confidence: 99%
“…Furthermore, hard carbon can also avoid the disadvantage of the high reactivity of graphitized carbon, which provides a new idea for modified graphite anode materials. Wang 27 and co-workers prepared CeO 2 @carbon hollow spheres by mild hydro-thermal reactions. The capacity retention of the hybrid material is enhanced by 27.0% after 120 cycles, and the CeO 2 @Carbon electrode still shows a reversible specific capacity of 119 mA h g −1 after 120 cycles at a current density of 200 mA.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that in energy conversion and storage aspects, catalysts alloying with rare-earth (RE) elements significantly influence their performance. Due to their unique electronic configurations, the rare-earth elements play an important role in tuning their functional properties from the perspective of electronic and catalytic activities. In view of the superior electrocatalytic activity of platinum in HER, the electrocatalytic performance can be enhanced by doping rare-earth elements into metallic platinum. The lanthanide series have similar atomic radii and electronic structure properties, so we can deduce that if platinum can form an alloy with one of the rare-earth elements (e.g., lanthanum), the other rare-earth elements can also form stable alloy phases as a result .…”
Section: Introductionmentioning
confidence: 99%